PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Ayu Retno Widyo Utami; Mukhroji Mukhroji (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Human resources are a very important part for the Company. Human resources who have good quality and work professionally will greatly assist the company in achieving its goals. PT. Cebong Kayuindo Ajibarang experienced a decline in employee performance. Therefore, further research is needed on the influence of work discipline and work environment on employee performance through job satisfaction as a mediating variable. This research was conducted at PT. Cebong Kayuindo Ajibarang. The data used are primary data obtained from distributing questionnaires with samples using the help of SmartPLS software version 4. The results of the study show 1). Work discipline does not affect employee performance 2). The work environment has a positive effect on employee performance. 3). Work discipline has a positive effect on job satisfaction 4). The work environment has a positive effect on job satisfaction 5). Job satisfaction has a positive effect on employee performance 6). Job satisfaction is able to mediate the relationship between work discipline on employee performance 7). Job satisfaction is able to mediate the relationship between work environment on employee performance.